Creating Promotional Mix and Improving Physical Evidence to Attract Potential Customers of Suci Shoelab - Bagaskara, Masyhuril Amri; Lupiyoadi, Rambat (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
The increasing number of MSMEs in Indonesia creates even more competition among businesses, especially during the COVID-19 pandemic. This difficult situation causes a decline in revenue and forces MSMEs in Indonesia to find strategies to survive. This study aims at helping an MSME in the shoe laundry industry called Suci Shoelab. This study employs qualitative and business coaching methods. The data were collected through interviews with the MSME owners and the employees as well as questionnaires given to customers. Several analytical methods, namely Business Model Canvas (BMC), Porter's Five Forces analysis, PESTEL analysis, Service Marketing Mix, SWOT analysis, TOWS analysis, Gap analysis, and Pareto Analysis, were used to identify the problems and generate solutions. The findings revealed that the MSME had not promoted its products consistently and the location of Suci Shoelab was unknown to many potential customers. The MSME improved the promotional activity and placed signage to enhance its physical evidence to address this issue. Sales promotions and digital/internet marketing were also used for the promotional mix, and discount prices and drop stations were applied as promotional programs. For increasing its physical evidence, the MSME placed signage at the store to attract potential customers. After the solutions were applied, the sales of the MSME increase.